Thai veterinarians' perceptions of cannabidiol products for dogs with osteoarthritis: a qualitative interview study - Nerapusee, Osot; Soontornvipart, Kumpanart; Pettong, Thanakrit; Phongsuchat, Nutkritta; Lunsucheep, Doungkamol; Patikorn, Chanthawat; Vimolmangkang, Sornkanok; Anantachoti, Puree (Frontiers in Veterinary Science, 2023)
Introduction: The global popularity of Cannabidiol (CBD) led to its approval for human use in Thailand and potential use in animals. Many studies revealed CBD's efficacy in treating chronic osteoarthritis (OA) in dogs. To facilitate tailored CBD product development for canine OA and ensure market success, this study explores Thai veterinarians' perception of CBD for canine OA. Methods: In-depth interviews were conducted with experienced veterinarians who treated OA in ≥25% of their canine patients. Interview questions covered treatment, CBD perception, and adoption. Interviews were held from January to March 2023. Results: Eleven out of twenty invited veterinarians participated in the study. Though all favored non-steroidal anti-inflammatory drugs (NSAIDs) for OA in dogs, concerns about adverse reactions, including ulcers and renal failure, emerged. CBD was widely known and was perceived positively for pain, inflammation, cancer, and epilepsy. However, half distinguished CBD from marijuana and tetrahydrocannabinol (THC). Ten expressed willingness to prescribe CBD for OA upon robust clinical evidence. Worries centered on product consistency and impurities. Many suggested CBD should be under veterinarians’ supervision at first, but this can be relaxing once safety and efficacy are established. CBD products should be chewable tablets, oils, or gelatin capsules with flavors like beef, liver, pork, fish, or seafood. Conclusion: Though CBD benefits were recognized, knowledge gaps among the participants persisted, warranting robust CBD safety, efficacy, and quality evidence to ensure Thai market success. Comprehensive education, including continuing education for those in practice and incorporating CBD-related topics into the Schools of Veterinary’s curriculum, is recommended.